THE INFLUENCE OF FOREIGN OWNERSHIP, INSTITUTIONAL OWNERSHIP, INDEPENDENT COMMISSIONERS, AND FINANCIAL DISTRESS TO STOCK PRICE WITH ACCOUNTING CONSERVATISM AS A MODERATION VARIABLE - Firmansyah, Andi; Syarifuddin; Darmawati (Assets: Jurnal Ekonomi, Manajemen, dan Akuntansi, 2023)
This study aims to analyze the influence of Foreign Ownership, Institutional Ownership, Independent Commissioners, and Financial Distress using the disclosure of Accounting Conservatism as a moderating variable. Data collection was obtained from the annual financial reports of Pharmacies listed on IDX 2017 – 2021 period, totaling 30 companies. The sampling technique used purposive sampling because the sample selection was based on the assessment of some of the characteristics of the sample members, which adjusted to the researcher’s intentions. Using secondary data on the official IDX website (www.idx.co.id) and the official website of each company. The data analysis method used a special application of multiple linear regression analysis using Moderated Regression Analysis (MRA) with a quantitative approach. The study results show that foreign ownership and independent commissioners do not affect stock prices. Institutional ownership and financial distress have a significant effect on stock prices. Foreign ownership and independent commissioners influence share prices moderated by accounting conservatism. Institutional ownership and financial distress do not affect stock prices of pharmaceutical companies moderated by accounting conservatism. From the results of this study, it is hoped that pharmaceutical sub-sector companies will consider financial reports in carrying out their operating activities. In addition, investors can be used as a tool that provides additional information.